Baicalin inhibits biofilm formation, attenuates the quorum sensing-controlled virulence and enhances Pseudomonas aeruginosa clearance in a mouse peritoneal implant infection model - Luo, Jing (PLoS One, 2017)
The quorum sensing (QS) circuit plays a role in the precise regulation of genes controlling virulence factors and biofilm formation in Pseudomonas aeruginosa. QS-controlled biofilm formation by Pseudomonas aeruginosa in clinical settings has remained controversial due to emerging drug resistance; therefore, screening diverse compounds for anti-biofilm or anti-QS activities is important. This study demonstrates the ability of sub-minimum inhibitory concentrations (sub-MICs) of baicalin, an active natural compound extracted from the traditional Chinese medicinal Scutellaria baicalensis, to inhibit the formation of Pseudomonas aeruginosa biofilms and enhance the bactericidal effects of various conventional antibiotics in vitro. In addition, baicalin exerted dose-dependent inhibitory effects on virulence phenotypes (LasA protease, LasB elastase, pyocyanin, rhamnolipid, motilities and exotoxin A) regulated by QS in Pseudomonas aeruginosa. Moreover, the expression levels of QS-regulatory genes, including lasI, lasR, rhlI, rhlR, pqsR and pqsA, were repressed after sub-MIC baicalin treatment, resulting in significant decreases in the QS signaling molecules 3-oxo-C12-HSL and C4-HSL, confirming the ability of baicalin-mediated QS inhibition to alter gene and protein expression. In vivo experiments indicated that baicalin treatment reduces Pseudomonas aeruginosa pathogenicity in Caenorhabditis elegans. Greater worm survival in the baicalin-treated group manifested as an increase in the LT(50) from 24 to 96 h. In a mouse peritoneal implant infection model, baicalin treatment enhanced the clearance of Pseudomonas aeruginosa from the implants of mice infected with Pseudomonas aeruginosa compared with the control group. Moreover, the combination of baicalin and antibiotics significantly reduced the numbers of colony-forming units in the implants to a significantly greater degree than antibiotic treatment alone. Pathological and histological analyses revealed mitigation of the inflammatory response and reduced cell infiltration in the peritoneal tissue surrounding the implants after baicalin treatment. Measurement of the cytokine levels in the peritoneal lavage fluid of mice in the baicalin treatment group revealed a decrease in IL-4, an increase in interferon γ (IFN-γ), and a reversed IFN-γ/IL-4 ratio compared with the control group, indicating that baicalin treatment activated the Th1-induced immune response to expedite bacterial load clearance. Based on these results, baicalin might be a potent QS inhibitor and anti-biofilm agent for combating Pseudomonas aeruginosa biofilm-related infections.